2021
DOI: 10.1002/brb3.2141
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte‐to‐lymphocyte ratio as a predictor of stroke‐associated pneumonia: A retrospective study‐based investigation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“… 13 In addition, the monocyte to lymphocyte ratio, a reverse ratio of LMR, was indicated to have a prognostic ability for stroke-associated pneumonia (SAP). 24 However, limited research investigated the predictive value of LMR for ICH prognosis. A small-sample and retrospective study showed LMR as a predictor for ND and 90-day mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 In addition, the monocyte to lymphocyte ratio, a reverse ratio of LMR, was indicated to have a prognostic ability for stroke-associated pneumonia (SAP). 24 However, limited research investigated the predictive value of LMR for ICH prognosis. A small-sample and retrospective study showed LMR as a predictor for ND and 90-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We also found an association between higher LMR values and a decreased risk of infections during hospitalization, which is in line with previous studies. 24 , 33 These findings provide a surrogate biomarker of the immune response induced by local cerebral hematoma and systemic inflammation, reflecting the likelihood of secondary brain injury and vulnerability to post-stroke infections. Accordingly, the early decrease of LMR values is driven by lymphocyte reduction and/or monocyte rise, which can enhance the reliable prediction of the risks of complicated infections, short-term mortality, and adverse functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… A study by Cheng et al 6 showed that higher monocyte-to-lymphocyte ratio (MLR) was significantly associated with SAP in AIS patients. Another study by Cao et al 7 shows that a high MLR is an independent risk factor for SAP and has a predictive value for severe pneumonia in patients with SAP. Compared to this article, the authors use neutrophils rather than monocytes in the ratio.…”
Section: Dear Editormentioning
confidence: 95%
“…A trained neurologist assessed the GCS and NIHSS scores at admission to assess the severity of SICH. The following formulae were used to compute the lymphocyte-based inflammatory index in this study: SIRI ( 21 ), NLR ( 15 ), MLR ( 14 ), and PLR ( 22 ) from the first peripheral blood count at admission.…”
Section: Methodsmentioning
confidence: 99%
“…Routine blood markers (i.e., neutrophils, lymphocytes, and monocytes) are common systemic inflammation and infection markers. In addition, the systemic inflammation response index (SIRI), neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR), and platelet/lymphocyte ratio (PLR) have better predictive power than conventional inflammatory factors ( 11 14 ). Most studies on risk factors for SAP are based on ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%